Citizenship Education Management Based on Character in Junior High Schools - Rosida Rosida; Hilal Mahmud; Taqwa Taqwa (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
This study aims to analyze and describe the model of character-based citizenship education management; the implementation of character-based citizenship education management; and the impact of the implementation of character-based citizenship education management in Junior High Schools. The research method used is qualitative. Data were collected through observation, interviews, student attitude journals, and documentation. Data were processed and analyzed using thematic analysis techniques, involving data condensation, data presentation, and drawing conclusions. The results of the research indicate that 1) the citizenship education model based on 'problem-based learning' is in line with the 2013 Curriculum, with a focus on character education and comprehensive student evaluation. The study materials are oriented toward shaping the character of the students. The form of the syllabus, lesson plans, the implementation of teaching, and the assessment procedures all adhere to the 2013 Curriculum. The implementation of character-based citizenship education management encompasses: lesson planning, teaching execution, and assessment implementation. The implementation of character-based citizenship education management has a significant impact on changing students' attitudes, behavior, and learning achievement.